OPTIMALISASI EDUKASI KESEHATAN REPRODUKSI REMAJA (PHBS) - Iin Setiawati; Zakkiyatus Zainiyah; Hamimatus Zainiyah (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Factor Clean and Healthy Living Behavior (PHBS) play an important role in determining degree of human health. PHBS can be interpreted as any behavior that is implemented consciously as a result of learning, which forms a person, family and community can be independent in the field of health and participate in realizing public health. In line with the health promotion center's report which states that 75% of public health is formed from healthy environments and PHBS. The implementation method was conducted counseling about PHBS in Nurul Karomah Peterongan Galis after which a questionnaire was given about PHBS. The results are the PHBS Habits of students Mostly good (66.67%), adolescent knowledge of PHBS Mostly good (77.19%), the role of teachers in PHBS Partly good (50.88%), the role of parents in good PHBS activities (63.16%) and the role of health personnel is all good (100%). In conclusion, implementation of PHBS in Nurul Karomah Peterongan Galis is good and has received support from teachers, parents and health workers.